2019
DOI: 10.1038/s41556-019-0433-z
|View full text |Cite
|
Sign up to set email alerts
|

Phase separation of YAP reorganizes genome topology for long-term YAP target gene expression

Abstract: Yes-associated Protein (YAP) is a transcriptional co-activator that regulates cell proliferation and survival by binding to a select set of enhancers for target gene activation. How YAP coordinates these transcriptional responses is unknown. Here, we demonstrate that YAP forms liquid-like condensates in the nucleus. Formed within seconds of hyperosmotic stress, YAP condensates compartmentalized YAP’s transcription factor TEAD1 and other YAP-related co-activators, including TAZ, and subsequently induced transcr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
277
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 297 publications
(294 citation statements)
references
References 53 publications
(97 reference statements)
16
277
1
Order By: Relevance
“…Perhaps the most striking aspect of HOPS is its rapid onset, which is faster than the speed of canonical stress responses . This feature is similar to recent reports of rapid nuclear condensation of DEAD-box RNA helicase DDX4 in response to environmental stress (Nott et al, 2015), and of transcriptional co-activator YAP in response to hyperosmotic stress (Cai et al, 2018). Notably, prolonged exposure to hyperosmotic conditions, similar to other environmental stressors, triggers the ISR and subsequent assembly of SGs, often localized adjacently to pre-formed DCP1A condensates or PBs (Figure 1) (Kedersha et al, 2005).…”
Section: Hops May Serve As a Rapid Cellular Sensor Of Volume Compressionsupporting
confidence: 89%
See 1 more Smart Citation
“…Perhaps the most striking aspect of HOPS is its rapid onset, which is faster than the speed of canonical stress responses . This feature is similar to recent reports of rapid nuclear condensation of DEAD-box RNA helicase DDX4 in response to environmental stress (Nott et al, 2015), and of transcriptional co-activator YAP in response to hyperosmotic stress (Cai et al, 2018). Notably, prolonged exposure to hyperosmotic conditions, similar to other environmental stressors, triggers the ISR and subsequent assembly of SGs, often localized adjacently to pre-formed DCP1A condensates or PBs (Figure 1) (Kedersha et al, 2005).…”
Section: Hops May Serve As a Rapid Cellular Sensor Of Volume Compressionsupporting
confidence: 89%
“…Both rapid and prolonged HOPS are reversible ( Figure 1) and can mediate widespread effects, including impairment of transcription termination ( Figure 6) (Vilborg et al, 2015), YAP-programmed transcription initiation (Cai et al, 2018), inhibition of ribosomal translocation (Wu et al, 2019), and modulation of RNA silencing (Pitchiaya et al, 2019). While other mechanisms may be also at play, protein sequestration away from the site of their function provides a straightforward biophysical explanation for many of these effects ( Figure 6).…”
Section: Hops May Serve As a Rapid Cellular Sensor Of Volume Compressionmentioning
confidence: 99%
“…Cytoskeletal structure and forces are now known to regulate nuclear transport of mechanosensitive transcriptional activators such as YAP and MRTF-A (23,44,45). Previously, YAP has been shown to undergo phase-mediated reorganization within nucleus and cytoplasm, which leads to upregulation of YAP-related transcription factors, such as TEAD1 (46). Upregulated YAP levels have also been shown to predict higher contractility in cancer associated fibroblasts, leading to matrix stiffening and cancer cell invasion (40).…”
Section: The Modelmentioning
confidence: 99%
“…These results suggest that Mask proteins can cluster/polymerise YAP to drive colloidal phase separation -a classic mechanism of cellular compartmentalisation (Hardy, 1899;Iborra, 2007;Walter and Brooks, 1995;Wilson, 1899). Recent work has shown that cells expressing GFP-tagged YAP can exhibit colloidal phase separation and formation of YAP liquid droplets in both nucleus and cytoplasm after treatment with 25% PEG to induce macromolecular crowding (Cai et al, 2018). Our findings indicate that endogenous YAP can also phase separate when it becomes stabilised and concentrated by clustering with Mask family proteins.…”
Section: Resultsmentioning
confidence: 95%
“…An interesting consequence of the role of Mask1/2 in stabilising YAP protein is that overexpression of Mask proteins is sufficient to dramatically raise the concentration of YAP within the cytoplasm, even causing formation of colloidal YAP liquid droplets in human cells. Similar YAP liquid droplets have recently been shown to occur by phase separation after treatment of cells expressing GFP-tagged YAP with 25% PEG to drive macromolecular crowding (Cai et al, 2018). Whether phase-separation of YAP has a physiological role is still unknown, but the possibility is supported by the fact that endogenous YAP can also be observed to phase separate when in a complex with Mask1 at high concentrations.…”
Section: Discussionmentioning
confidence: 91%